2014
DOI: 10.1002/oby.20954
|View full text |Cite
|
Sign up to set email alerts
|

FABP4 is secreted from adipocytes by adenyl cyclase-PKA- and guanylyl cyclase-PKG-dependent lipolytic mechanisms

Abstract: Objective: Fatty acid-binding protein 4 (FABP4) is expressed in adipocytes, and elevated plasma FABP4 levels are associated with obesity-mediated metabolic phenotype. Postprandial regulation and secretory signaling of FABP4 have been investigated. Methods: Time courses of FABP4 levels were examined during an oral glucose tolerance test (OGTT; n 5 53) or a high-fat test meal (n 5 35). Effects of activators and inhibitors of adenyl cyclase (AC)-protein kinase A (PKA) signaling and guanylyl cyclase (GC)-protein k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
106
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(113 citation statements)
references
References 31 publications
7
106
0
Order By: Relevance
“…FABP4 is secreted from adipocytes under regulation by the catecholamine‐induced lipolytic signal pathway, although FABP4 lacks an N‐terminal secretory signal sequence 7, 12, 13. The present study showed that secretion of FABP4 from endothelial cells was slightly, but significantly, enhanced by stimulation of isoproterenol, similar to that in the case of adipocytes.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…FABP4 is secreted from adipocytes under regulation by the catecholamine‐induced lipolytic signal pathway, although FABP4 lacks an N‐terminal secretory signal sequence 7, 12, 13. The present study showed that secretion of FABP4 from endothelial cells was slightly, but significantly, enhanced by stimulation of isoproterenol, similar to that in the case of adipocytes.…”
Section: Discussionsupporting
confidence: 71%
“…FABP4 was secreted from HCAECs in a time‐dependent manner (Figure 2I), and the secretion of FABP4 was slightly, but significantly, enhanced in the presence of isoproterenol for 12 and 24 hours, which is known to increase secretion of FABP4 from adipocytes 12, 13. Secretion of FABP4 in the CM of Ad‐FABP4–transfected HCAECs was significantly greater than that in the CM of Ad‐Control–transfected HCAECs (Figure 2J).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…correlated with adiposity (Xu et al 2006, Ishimura et al 2013. Despite its lack of an N-terminal secretory signal sequence (Furuhashi & Hotamisligil 2008), FABP4 has been reported to be released from adipocytes through additional mechanisms (Coe et al 1999, Scheja et al 1999, Shen et al 1999, Mita et al 2015 and acts as an adipokine in several organs, including the heart (Fig. 2).…”
Section: Figurementioning
confidence: 99%